(untitled) (UCC Student Medical Journal, 2024)
Introduction: JM, a 20-year-old male professional ice hockey player, presented with a 2-week history of lack of range of motion, weakness, and pain in his right knee, after a 2-year post-medical collateral ligament repair of the right knee and 3 year-post anterior cruciate ligament, posterior cruciate ligament and medial collateral ligament reconstruction of the right knee. Case Description: In the course of history taken, it was revealed that 5 months prior to admission the patient had been informed by a psychiatrist that he had sport-related anxiety. With an unremarkable psychiatric history prior to age 18, the competitive nature of his sports career in addition to financial pressure may have contributed to his sports-related anxiety. His examination findings were consistent with a diagnosis of complete tears of the right anterior cruciate ligament and posterior cruciate ligament along with grade III medial collateral ligament injury. Discussion: The biopsychosocial model was used to explicate JM’s case. JM’s current injuries prompted reconstruction of the anterior cruciate, posterior cruciate, and medial collateral ligaments. Psychologically, JM’s sports-related anxiety is not a rare phenomenon as recent studies have discovered an increased risk of sports-related anxiety amongst young professional athletes. Sports-related anxiety, along with competitive trait anxiety, may be factors that contribute to sports injury occurrence. Other psychological stressors can add to sports-related or competitive trait anxiety, further increasing the risk of sports injury reoccurrence. Summary: JM was admitted for a right knee open medial collateral ligament repair with internal bracing, anterior cruciate ligament reconstruction, posterior cruciate ligament reconstruction, and platelet rich plasma injection. As part of a holistic patient-centered treatment plan, a referral to psychiatry was made to address JM’s sports-related anxiety with the goal of decreasing future risk of sports injury. Patient’s Consent Obtained: Yes